Employer awareness towards the importance of SOCSO protection / Maisarah Ab Razak - Ab Razak, Maisarah (Faculty of Business and Management, 2011)
This research conducted focusing on the “Employer awareness towards the importance of SOCSO protection”. As a social security in Malaysia, SOCSO realize that employer awareness is important to ensure that all workers especially Malaysian should know about functions and benefits provided by SOCSO. The main objectives of this study are (1) to identify the level of employer awareness towards the importance of SOCSO protection, (2) to identify the significant relationship between dependent variable and each independent variable, (3) to identify the most significant factor that influence the employer awareness towards the importance of SOCSO protection. The respondents of this study were employer in Batu Pahat. 50 questionnaires had been distributed among them. The researcher had used convenience sampling as sampling technique. The process of analyzing and interpreting data has been presented with tables using method as reliability test, frequency and descriptive analysis. The researcher also had come out with few recommendation can be taken into consideration. By implementing these recommendations, it will help SOCSO to upgrade their management for SOCSO future in order to increase the employer awareness towards the importance of SOCSO protection.